KORELASI ANTARA KUALITAS PERAIRAN DAN TINGKAT PREVALENSI BAKTERI PATOGEN PADA IKAN MAS YANG DIBUDIDAYAKAN DI WADUK KOTO PANJANG KABUPATEN KAMPAR - Risman Ferdiansyah; Syafruddin Nasution; Henni Syawal (Program Pascasarjana Universitas Riau, 2016)
Utilization of Koto Panjang reservoir for common carp (Cyprinus carpio) breeding using floating net cages is increasing. This results in a decrease of water quality and infectious bacterial disease. The lack of information about the diversity of pathogenic bacteria and the prevalence of pathogenic bacteria , led to the need for studies to observe the relationship between the incidence of diseases caused by pathogenic bacteria with the water quality parameters. This study aims to determine the quality of the waters, inventory pathogenic bacteria, as well as knowing the correlation between water quality parameters with the prevalence of pathogenic bacteria in common carp in Koto Panjang reservoir. Location of the study included five observation stations (Dam Site, Pulo Gadang, Batu Langkah Besar, Muara Mahat, and Tanjung Alai) with three sampling periods. Water quality parameters measured were temperature, pH, Dissolved Oxygen, Nitrate, Nitrite, Ammonia, Phosphate, Total Suspended Solids, and Biological Oxygen Demands. Result of water quality measurements showed that the water quality was still good and the water was still in the range of quality standards required, except for the content of ammonia which was already passed the threshold. The pathogenic bacteria in common carp were Aeromonas sp, Pseudomonas sp, Yersinia sp and Pasteurella sp., While on the water samples were Pseudomonas sp, Enterobacter sp, Vibrio sp, Aeromonas sp, Streptococcus sp, and Staphylococcus sp. The correlation between the prevalence of pathogenic bacteria and water quality parameters was vary, Aeromonas sp was weakly correlated (32.3%), while the prevalence of Pseudomonas sp had a strong relationship (81.3%). The correlation between the total bacteria and water quality had a strong connection, water quality parameters were measured at 64.8% affected total bacteria and 35.2% were influenced by other factors.